THE DEVELOPMENT OF KINEMASTER APPLICATION-BASED LEARNING VIDEOS TO IMPROVE STUDENTS' BEGINNING READING AND WRITING SKILLS GRADE II SD - Maelani, Rinda (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
The research objectives (1) to produce a learning video media design for grade II elementary school students, (2) to know the learning video development process (3) to know the implementation of reading and writing learning videos, (4) to know the assessment of student learning videos. The research was conducted in Bantul and Kulon Progo districts in the 2022/2023 academic year with 44 students. This research is a development research with ADDIE model. The data analysis technique used are a linkert scale and N-Gain Score. The results of this study (1) Validation design from media experts gets a score of 4 very good criteria, (2) development of learning videos with 5 stages, namely analyzing data, designing video designs, developing design results, implementing products to students, analyzing assessments (3) product implementation got quite effective criteria with a score of 64.5833, for writing 80.0747 effective criteria for SD Negeri Kembang. SD Negeri Rejodadi reading results get71.4557 fairly effective criteria, writing 67.0873 fairly effective criteria, (4) assessment of learning videos from student questionnaires results get 89% for SD Negeri Rejodadi and 86% SD Negeri Kembang very practical category.